3D-printed surgical wound dressing for prolonged 5-fluorouracil delivery from pluronic blending composites. (December 2022) - Lin, Tz-Feng; Huang, Yi-Jen; Liu, Yi-Jui; Peng, Cheng-Ming; Juan, Chun-Jung; Yeh, Shih-Hsuan; Chou, Ruey-Hwang
Abstract: A direct drug delivery system of with the inhibition of multidrug resistance was developed in this study by the polymer mixing of Pluronic block copolymer F127, L121, polyethylene glycol (PEG), and polyvinyl alcohol (PVA). The polymer mixing was defined as Pluronic blending composites (PBCs) and optimized through adjusting the ratio of two different water-soluble homopolymers, PEG and PVA. The chemotherapeutic drugs of 5-fluorouracil (5-FU) were released from Pluronic blending composites nearly one month without continuous supplementary. Also, the effective ingredient of L121 inhibited multidrug resistance in human pancreatic cancer and caused the malfunction of the ATP binding cassette subfamily C (ABCC) transporter as evidenced by the flow cytometer studies. PBC-3 effectively suppresses the function of ABCC transporter up to 25 days. 5-FU are able to accumulate in the cancer cells of AsPC-1 and PANC-1 at a designated effective concentration. Then, a surgical dressing was prepared by 3D bio-printing technology with Pluronic blending composites cross-linked by sodium alginate. Results show that the surgical dressing of 24 layers with 10 mm × 10 mm would continuously release 5-FU in effective anticancer concentration for six days. Graphical Abstract: ga1 Highlights: 3D bio-printing surgical dressing prepared by Pluronic blending composites (PBCs). A direct drug delivery system of 5-fluorouracil (5-FU) embedded in PBCs. 5-FU was slowly released from PBCs more than 25 days. The function of a multi-drug resistance regarding ABCC transporter was inhibited. Resectable cancer site treatment is effective to suppress the recurrence of pancreatic cancer.